Choice of Law for Equitable Doctrines - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2004)
Deals with the legal questions relating to the applicable law that arise in cross-border litigation when litigants invoke the principles of English equity or analogous doctrines from other jurisdictions. This book analyzes the various different ways in which equitable doctrines can be characterised.